Virtual Banks: The Innovative Way of the Banking System Development during the Crisis - Alexey V. Bataev (International Review of Management and Marketing, 2016)
The paper deals with development of a new form of banking financial institutions – the virtual banks. The main trends and perspectives of the virtual banks development in crisis conditions in Russia and in the world are analyzed. Forms and types of the virtual banks are considered. The analysis of client’s interaction with the virtual banks models is carried out; revealed their advantages to business. The assessment of the virtual financial institutions development in the Russian banking system is made. The comparative analysis of the virtual banks with classical financial institutions is carried out.